Anthropometric Measurements And Their Relationship With Motor Chain Artistic Performance In Artistic Gymnastics For Third Year Female Students of Physical Education And Sport Sciences/ Basra University 2016 – 2917 - Essa, Kadhim; Hussein, Mahassen (Journal of Physical Education, 2017)
The aim of the research is to identify the anthropometrical measurements of motor chain in artistic gymnastics in third year female students. In addition to that, the researchers aimed at identifying the motor chain in the artistic gymnastics of third year female gymnastics as well as identifying the relationship between anthropometric measurements and the artistic performance of motor chain in third year female students in artistic gymnastics. The researchers used the descriptive method. The subjects were (38) third year female students; (20) from section g and (18) from section (h). The data was collected and treated using proper statistical operations to come up with the conclusions. The researchers concluded that there is a significant correlation relation between height, weight and motor chain artistic performance as well as a significant correlation between width of waist, chest and hip with motor chain artistic performance. Finally the researchers recommended including teaching units to improve anthropometric and physical qualities in students that affect their performance and encouraging students to do physical exercises due to their positive effect on the body and performance